Development of Flexible Fluidised-bed Gasification Process for Co-production of Synthesis Gas and Biochar - Esa Kurkela; Minna Kurkela; Sanna Tuomi; Ilkka Hiltunen (Chemical Engineering Transactions, 2024)
In the FlexSNG project, a fluidized-bed gasification process is developed that can co-produce biochar and good-quality synthesis gas and can also switch between two operation modes: (1) co-producing biochar and synthesis gas that is further converted to biomethane or other synthesis products, and (2) maximizing the fuel conversion to syngas. Three test runs were conducted at an atmospheric-pressure Circulating Fluidized-Bed (CFB) gasification test rig of VTT to identify optimal gasification and gas clean-up process conditions for both operation modes. The studied gasification process consists of a fluidized-bed gasifier, a hot gas filter and a catalytic reformer. The tests were focused on finding optimal process conditions in the gasifier for the co-production of biochar and synthesis gas from woody residues and straw. Two different operating principles were examined: an ordinary CFB gasifier operated at different temperatures and a so-called Bubbling Circulating Fluidized-Bed (BCFB), in which the lower part of the gasifier is operated at low temperature and secondary oxygen is used to raise the temperature in the upper part of the gasifier.